Estradiol variability is associated with brain structure in early adolescent females. (December 2022) - Zwaan, Isabel S.; Felmingham, Kim; Vijayakumar, Nandi; Patton, George; Mundy, Lisa; Byrne, Michelle L.; Simmons, Julian; Whittle, Sarah
Abstract: One-third of adolescents are diagnosed with a psychiatric disorder by age 16, with female adolescents twice as likely to experience an internalizing (i.e., depression or anxiety) disorder as their male peers. Individual differences in pubertal factors may partially underlie this disparity, potentially via the role of pubertal hormones in shaping brain development. While research has examined links between estradiol levels and brain structure, individual variation in estradiol levels has not been considered. Using longitudinal data from 44 female adolescents (baseline age M = 11.7; follow-up age M = 13.3), we examined associations between both average estradiol and estradiol variability, and brain gray matter structure at baseline. We used a hypothesis-driven region of interest (ROI) approach focusing on subcortical and ventromedial prefrontal regions, in addition to an exploratory whole-brain analysis. We also investigated whether brain structure mediated the association between estradiol measures and internalizing (i.e., anxious and depressive) symptoms at follow-up. ROI analyses revealed a significant negative association between estradiol variability and thickness of the right medial orbitofrontal cortex (OFC, β = −0.39, FDR corrected p = .010). There were, however, no significant associations between average estradiol or estradiol variability and internalizing symptoms, nor was there evidence of mediation. Our results indicate that increased variation in estradiol levels across a month is associated with decreased cortical thickness in a brain region implicated in emotion processing, although implications for mental health are unclear. Findings, however, highlight the importance of considering individual variation in estradiol when examining links to brain development. Highlights: Estradiol variability may be a more useful measure than average or total levels. Estradiol variability is associated with brain structure in female adolescents. Estradiol variability predicts right OFC thickness, mean estradiol does not.